Math Anxiety and Self-Efficacy on Students' Relational Understanding Ability - Salamah, Mujibah; Wawan, Wawan; Ningsih, Eka Fitria (Delta-Phi: Jurnal Pendidikan Matematika, 2023)
This research aims to determine the influence of math anxiety and self-efficacy on relational abilities. This research is quantitative research with correlational methods. The research population included all class XI students at one of the vocational high schools in Metro City. The study consisted of 29 students using a cluster random sampling technique. The instruments for math anxiety and self-efficacy use questionnaires, while the instruments for relational understanding abilities use tests. The data analysis technique uses multiple linear regression. The analysis shows that math anxiety and self-efficacy significantly influence 79% of relational understanding abilities. Math anxiety has a negative but insignificant influence on relational abilities (r = -0.053 sig. = 0.60), while self-efficacy has a positive and significant influence (r = 0.655 sig. = 0.00). This research implies that it is essential to increase the self-efficacy of each student. Teachers must strive for activities supporting students' self-efficacy, such as providing motivation and guidance during mathematics lessons.